Layer-by-Layer Assemblies of Catechol-Functionalized TiO2 Nanoparticles and Porphyrins through Electrostatic Interactions - Burger, Alexandra; Costa, Ruben Dario; Lobaz, Volodymyr; Peukert, Wolfgang; Hirsch, Andreas; Guldi, Dirk Michael (Chemistry - A European Journal, 2015)
In the current work, we present the successful functionalization and stabilization of P-25 TiO2 nanoparticles by means of N1,N7-bis(3-(4-tert-butyl-pyridium-methyl)phenyl)-4-(3-(3-(4-tert-butyl-pyridinium-methyl)phenylamino)-3-oxopropyl)-4-(3,4-dihydroxybenzamido)heptanediamide tribromide (1). The design of the latter is aimed at nanoparticle functionalization and stabilization with organic building blocks. On one hand, 1 features a catechol anchor to enable its covalent grafting onto the TiO2 surface, and on the other hand, positively charged pyridine groups at its periphery to prevent TiO2 agglomeration through electrostatic repulsion. The success of functionalization and stabilization was corroborated by thermogravimetric analysis, dynamic light-scattering, and zeta potential measurements. As a complement to this, the formation of layer-by-layer assemblies, which are governed by electrostatic interactions, by alternate deposition of functionalized TiO2 nanoparticles and two negatively charged porphyrin derivatives, that is, 5,10,15,20-(phenoxyacetic acid)-porphyrin (2) and 5,10,15,20-(4-(2-ethoxycarbonyl)-4-(2-phenoxyacetamido)heptanedioic acid)-porphyrin (3), is documented. To this end, the layer-by-layer deposition is monitored by UV/Vis spectroscopy, scanning electron microscopy, ellipsometry, and profilometry techniques. The resulting assemblies are utilized for the construction and testing of novel solar cells. From stable and repeatable photocurrents generated during several ön-offc̈ycles of illumination, we derive monochromatic incident photo-to-current conversion efficiencies of around 3 \